2013
DOI: 10.1175/jas-d-12-083.1
|View full text |Cite
|
Sign up to set email alerts
|

Latent Heating and Cooling Rates in Developing and Nondeveloping Tropical Disturbances during TCS-08: TRMM PR versus ELDORA Retrievals*

Abstract: Unique sets of Electra Doppler Radar (ELDORA) observations in both developing and nondeveloping tropical disturbances in the western North Pacific are used to retrieve latent heating and cooling rates. During the reintensification of Sinlaku, maximum heating rates of about 80 K h 21 are diagnosed in the upper troposphere in the region of a strong updraft and maximum cooling rates of about 245 K h 21 are diagnosed in the lower troposphere in the region of a strong convective-scale downdraft. The southern convec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…This increased the negative impact potential of downdrafts (i.e., increased DCAPE). Consistent with this assumption, Park and Elsberry (2013) concluded that evaporative cooling and strong downdrafts counteracted low-level spinup for TCS025 based upon an examination of latent heating and cooling rates retrieved from ELDORA radar during IOP-3. Molinari et al (2013) hypothesized that repeated lulls in convective activity for Tropical Storm (TS) Edouard (2002) were a result of vertical wind shear-induced ventilation that caused low-u e air to be transported into the boundary layer via downdrafts.…”
Section: Discussionmentioning
confidence: 89%
“…This increased the negative impact potential of downdrafts (i.e., increased DCAPE). Consistent with this assumption, Park and Elsberry (2013) concluded that evaporative cooling and strong downdrafts counteracted low-level spinup for TCS025 based upon an examination of latent heating and cooling rates retrieved from ELDORA radar during IOP-3. Molinari et al (2013) hypothesized that repeated lulls in convective activity for Tropical Storm (TS) Edouard (2002) were a result of vertical wind shear-induced ventilation that caused low-u e air to be transported into the boundary layer via downdrafts.…”
Section: Discussionmentioning
confidence: 89%
“…Among the channels, polarized corrected temperature (PCT) at 85 GHz is used in this study since it responds to ice scattering in the deep convective towers. The TMI TBs at 85.5 GHz have effective fields of view of 7 km 3 5 km (Park et al 2007). …”
Section: Datasetsmentioning
confidence: 99%
“…When the strong large-scale southwesterlies are present over the South China Sea owing to the eastward movement of the MJO over the western North Pacific (section 4), the primary area in which most of the MCSs and heavy precipitation originate is upstream and over the Philippines (Hoyos and Webster 2007;Ho et al 2008;Park et al 2011). Based on an analysis of eight years of TRMM PR rain rates, Ho et al (2008) found out that the diurnal maximum of rainfall during the WWB period occurs in the late morning.…”
Section: A Diurnal Evolution Of Mcss During Formation (24-27 Septembmentioning
confidence: 99%
See 2 more Smart Citations